The Role of the School Counselor in Diagnosing the Aggressive Behavior and Learning Disabilities: A Case Study in Algeria - Eddine, Mhamel Imad (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Observation is among the primary methods and tools used for data collection. It allows the researchers to do so when the data are generated in the real world and participate in the process as participant observers. In this line, the researcher records what he notices. Therefore, the observation is mainly related to the qualitative research and data. Nevertheless, the quantitative indices are a form of observation at the superficial level. It is also better to link the observation with the quantitative research design. This study aims to contribute to the understanding of observation in scientific research due to the low use of this technique in educational and psychological scientific research. Thus, the researcher carried out a theoretical reading of this tool and used the clinical method by presenting a practical model of observation to diagnose the psychological and educational issues in the school milieu. In this context, we studied a case that showed aggressive behaviors and relied on other tools to help diagnose the problem, such as the Harris Good-Enough test of man drawing and the scale of measuring learning disabilities made by Maamria Bashir in 2005. Findings show the efficiency of the observation in diagnosing the problem of aggressive behavior in the school milieu. Based on the results, we provided a set of recommendations and suggestions.